2008
DOI: 10.1016/j.ympev.2008.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Complete plastid genome sequence of the chickpea (Cicer arietinum) and the phylogenetic distribution of rps12 and clpP intron losses among legumes (Leguminosae)

Abstract: Chickpea (Cicer arietinum, Leguminosae), an important grain legume, is widely used for food and fodder throughout the world. We sequenced the complete plastid genome of chickpea, which is 125,319 bp in size, and contains only one copy of the inverted repeat (IR). The genome encodes 108 genes, including 4 rRNAs, 29 tRNAs, and 75 proteins. The genes rps16, infA, and ycf4 are absent in the chickpea plastid genome, and ndhB has an internal stop codon in the 5′exon, similar to other legumes. Two genes have lost the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
206
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(220 citation statements)
references
References 84 publications
(120 reference statements)
14
206
0
Order By: Relevance
“…Six complete legume chloroplast genomes have been reported to date (G. max, L. japonicus. M. truncatula, P. vulgaris, C. arietinum, and V. radiata) (Jansen et al, 2008;Tangphatsornruang et al, 2010). A similar tendency to lose the cp rps16 in selfcompatible plants is observed in these species.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Six complete legume chloroplast genomes have been reported to date (G. max, L. japonicus. M. truncatula, P. vulgaris, C. arietinum, and V. radiata) (Jansen et al, 2008;Tangphatsornruang et al, 2010). A similar tendency to lose the cp rps16 in selfcompatible plants is observed in these species.…”
Section: Discussionsupporting
confidence: 56%
“…Although the number of genes and their order are generally conserved among angiosperm chloroplast genomes, exceptional gene losses have been identified (e.g., rpl33 in Phaseolus vulgaris (Guo et al, 2007) and Vigna radiata (Tangphatsornruang et al, 2010), infA in almost all rosid species (Millen et al, 2001), rpl32 in the Populus genus (Okumura et al, 2006;Steane, 2005), rps16 in Medicago truncatula (Saski et al, 2005), P. vulgaris (Guo et al, 2007), Cicer arietinum (Jansen et al, 2008), V. radiata (Tangphatsornruang et al, 2010), and the Populus genus (Okumura et al, 2006;Steane, 2005)). It is also possible that genes that have been transferred or substituted recently in evolution remain in the chloroplast genome as remnants when gene transfer or substitution has occurred.…”
Section: Introductionmentioning
confidence: 99%
“…In tobacco, for example, 20 group II introns have to be spliced to enable the generation of translatable transcripts. Individual intron losses, for example, for the clpP, rpl2, rps12 and atpF genes have been recorded in a few angiosperm lineages (Schmitz-Linneweber et al 2001;Jansen et al 2008), but can generally be considered an exception. Therefore, it came as a surprise when the sequence analysis of the plastomes of C. gronovii (Funk et al 2007) and later also C. obtusiflora (McNeal et al , 2009) revealed the most extensive intron losses ever detected in any species: In both cases, all but one group IIa intron-intron 2 of clpP-were lost.…”
Section: Loss Of Introns In Cuscutamentioning
confidence: 99%
“…25 kb). The clade includes all the members of the tribes Cicereae, Hedysareae, Trifolieae, and Vicieae, as well as at least three other genera (Wojciechowski 2006 ;Jansen et al 2008 ). Thus, the interesting crop legume genera such as Trifolium, Medicago , and Cicer all hold a close phylogenetic relation to lentil and other Vicieae species.…”
Section: The Genus Lens Millermentioning
confidence: 99%